The natural food composition of long-tailed macaque (Macaca fascicularis Raffles, 1821) inhabiting the Muara Angke Wildlife Reserve in North Jakarta - Alvita Dwi Lestari; Felana Afifah; Dinda Kinanti; Shinta Alief Fitrianingtyas; Nur Azzizah Firdaus; Nabilah Nailiyah Isna; Dinda Devia; Fajar Nur Hasanah; Ade Basyuri; Yusuf Muhammad (LPPM Universitas Negeri Jakarta, 2024)
Long-tailed macaque (Macaca fascicularis) is one species of wild animals inhabits Muara Angke Wildlife Reserve (SMMA), a wetland reserve predominantly grown by mangrove swamp forest. As there is high encounter of M. fascicularis with human and high incident of human-given food, it is important to understand the composition of natural food of M. fascicularis. The method used was quantitative with data collection techniques using scan sampling technique with 5-minute intervals. Natural food source for M. fascicularis in SMMA is provided by 17 species of plants. The main natural food sources providing both leaves and fruits are Ficus benjamina (54.62%) and Sonneratia caseolaris (28.9%). The most common plant parts eaten by M. fascicularis are leaves (61%) and fruit (21%), resembles to those of leaf monkeys (langurs). However, is a high possibility that nutrient needed to supplement high leaf consumption in SMMA monkeys is provided by non-natural human-given food.